Formas y equilibrios del manganeso en suelos de América Central - FASSBENDER, H.W.; Roldan, J. A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Analizing eleven soils from the easternareas of the Central Platean of Costa Rica it was found that: 1) Drying soil samples induced a decrease of water soluble manganese. The topsoil and subsoil averaged 0.30 and 0.64 ppm in fresh samples respectively, while only traces could be determined in the air dryed topsoil and subsoil samples. 2) Exchangeable manganese (NH4 AcO, 1N, pH 7.0) increased after airdrying the soil samples, e g form 2.3 and 1.9 ppm for topsoil and subsoil to 11.5 and 2.5 respectively. 3) Reducible manganese (NH4 AcO + 2 per cent hydrochinone) showed no variation upn drying. 4) The amount of "exchangeable" manganese varied significantly with the pH (7.0 or 4.8) of the extractor (Nh4 AcO, 1N) 5) The hydrochinone produced no interference on the manganese determination by atomic absorption spectrometry. The analysis of manganese in 62 samples of Central American soils (mainly fluvisols 21, andosols 17, other soils 24), showed little variation with respect to Mn forms. For water soluble, exchangeable and reducible manganese, fluvisols contained averages of 2.64, 13.18 and 33.3 ppm. In general the values for the soil groups showed great variation, However some significant relationships (1 per cent level) such as between manganese forms, exchangeable Mn and pH (R = 0.342), reducible Mn and clay content (R = 0.481) and water soluble manganese and organic matter (R = 0.555) were found.